THE EFFECT OF PROMOTION MIX OF THE OFF-AIR ENGLISH SERVICE PROGRAM AT RRI PRO2 FM BANDUNG UPON THE LOYALTY OF THE AUDIENCES - Indra Dermawan (The Management Journal of Binaniaga, 2018)
This research aims to figure out how the effect of promotion mix of the Off Air English Service Program (ESP) at RRI Pro2 FM Bandung upon the loyality of its audiences, in order to communicate the Off Air English Service Program (ESP) to the audiences of at RRI Pro 2 FM Bandung, RRI has been doing the activity of promotion mix. Referring to Kotler & Armstrong (2008:166), promotion mix is also named Marketing Communication Mix, having the promotion mix the company could communicate the value of the audiences persuasively and develop the relationship with the customers. The writer has applied the theory of Kotler (2009:175) about the promotion mix (marketing communication mix) consisting of eight tools of promotion mix as the basic of the reseach which is promotion, marketing promotion, events and experiences, public relation and publicity, direct marketing, interactive marketing, mouth to mouth marketing, personal selling. Loyalty variable as Y variable, the writer has applied the theory from Grifin (2002:31) the audiences loyalty consists of four characters: (1) makes regular repeat purchase, (2) purchases across products or services line, (3) recommends other products (refers other), and (4) demonstrates on immunity to the full of the competition. Griffin (2002:31). Result of the analysis in this research has applied the method of SEM analysis (Structure Equation Models) indicating that the promotion mix has significantly affected the loyalty of audiences which is 61.9%, however the rest of 38.1% is the contribution of other variables that is not studied. Key words: Promotion Mix, Loyalty of The Audiences.